PROBLEMATIK PENDIDIKAN BAHASA INDONESIA KAJIAN PEMBELAJARAN BAHASA INDONESIA PADA SEKOLAH DASAR - Anisa Siti Nurmayasari; Cucu Siti Sumiati; Heri Husni; Nurfitria, Nurfitria (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Learning is a permanent change in student behaviour through experience, observation, and the use of language, which is done actively and relates to knowledge, attitudes, and skills. This study aims to explain the issues in Indonesian language education, especially regarding how students learn the language in the context of learning Indonesian. The method applied in this study is descriptive qualitative. The main data was obtained through interviews with teachers and parents. Observations were carried out to identify problems faced by students in learning Indonesian. The results showed that in the language learning process at school, especially at the primary school level, teachers conducted evaluations and understood that students had acquired language before entering school through the surrounding environment. Students tend to be more confident in learning a language if given the opportunity to improve through their own work. Language learning also provides opportunities for students to choose the language activities they want.